Anthologies and Black Poetry in Cuba: Revisiting Ramón Guirao’s Órbita de la poesía afrocubana (Islas, 2026)
Introduction: This article examines the role of Ramón Guirao’s anthology Órbita de la poesía afrocubana in legitimizing Afro-Cuban poetry within the literary canon of twentieth-century Cuba. The study focuses on how the work articulated debates on identity, race, and culture during the Republican period, highlighting its relevance to Afro-diasporic cultural and literary studies.Methods: A qualitative documentary analysis methodology was employed. The anthology’s structure, selection of texts, and the compiler’s prologue were examined. A hermeneutic approach made it possible to contextualize the work within the avant-garde movement and to contrast it with secondary sources on Black poetry and contemporary anthologies.Results: The anthology helped consolidate an Afro-Cuban poetic canon by including key authors and texts drawn from oral tradition. It privileged a folklorist and musical orientation over poetry centered on social protest. Guirao predominantly included white authors, reflecting the limited access of Afro-descendant writers to publication during the period. The glossary and other paratextual elements sought to universalize the work while simultaneously constructing the Afro-descendant subject as an “Other” requiring presentation and explanation.Conclusions: Órbita de la poesía afrocubana played a fundamental role in legitimizing Afro-Cuban poetry within the Cuban literary canon, although its folklorist and selective approach reflected the contradictions of its historical context. The anthology served as a precedent for subsequent compilations and highlighted the tension between authentic representation and cultural mediation.
Keywords: Afro-Cuban poetry; literary canon; avant-garde; anthology; Cuban literature; Afro studies